2
$\begingroup$

I have been working on the following question for a couple of days, and I am not getting anywhere. Suppose $A\in M_{n}$ with singular values $\sigma_{1}\geq \sigma_{2} \geq \cdots \sigma_n$. How can I show the following? $$\sigma_{1}\leq 1 \iff\begin{pmatrix}I_{n} & A \\ A^{*} & I_{n} \\ \end{pmatrix} \geq 0$$

$\endgroup$
3
$\begingroup$

(i) $\sigma_1 \leq 1 \implies B = \begin{pmatrix}I_{n} & A \\ A^{*} & I_{n} \\ \end{pmatrix} \geq 0$:

Consider any non-zero $x \in \mathbb{C}^{2n \times 1}$. Let $x = \begin{pmatrix} x_1 \\ x_2 \end{pmatrix}$ where $x_1,x_2 \in \mathbb{C}^{n \times 1}$. Then $$x^* Bx = \|x_1\|^2 + \|x_2\|^2 + x_1^*Ax_2 + x_2^*A^*x_1 = \|x_1\|^2 + \|x_2\|^2 + 2 \text{Re}(x_1^*Ax_2)$$ We have that $$|x_1^*Ax_2| \leq \|x_1\|\cdot\|Ax_2\| \leq \sigma_1 \|x_1\|\cdot\|x_2\|.$$ We also have that $$-|x_1^*Ax_2| \leq \text{Re}(x_1^*Ax_2) \leq |x_1^*Ax_2|.$$Hence, we get that $$x_1^*Ax_2 + x_2^*A^*x_1 = 2 \text{Re}(x_1^*Ax_2) \in \left[ -2 \sigma_1 \|x_1\|\cdot\|x_2\|,2 \sigma_1 \|x_1\|\cdot\|x_2\| \right].$$ Hence, $$x^* Bx \geq \|x_1\|^2 + \|x_2\|^2 - 2\sigma_1\|x_1\|\cdot\|x_2\| \geq 0 \qquad(\text{since }\sigma_1 \leq 1)$$

(ii) $B = \begin{pmatrix}I_{n} & A \\ A^{*} & I_{n} \\ \end{pmatrix} \geq 0 \implies \sigma_1 \leq 1$:

Since $B$ is given to be positive semi-definite, any non-zero $x \in \mathbb{C}^{2n \times 1}$ satisfies $x^*Bx \geq 0$. Consider $x = \begin{pmatrix} -u \\ v \end{pmatrix}$ where $u \in \mathbb{C}^{n \times 1}$ is the first left singular vector of $A$ and $v \in \mathbb{C}^{n \times 1}$ is the first right singular vector of $A$. Then $$0 \leq x^* Bx = \|u\|^2 + \|v\|^2 - u^*Av - v^*A^*u = 2 - 2 \sigma_1.$$ Hence, we get that $$\sigma_1 \leq 1.$$

| cite | improve this answer | |
$\endgroup$
4
$\begingroup$

This is a typical application the nonstrict Schur Complement Formula.

Basically the following are equivalent (two of them are trivially true): $$ \begin{pmatrix} I &A\\ A^* &I \end{pmatrix} \succeq 0 \iff \begin{align} I &\succeq 0\\ I - A^* I A &\succeq 0\\ A(I-I) &= 0 \end{align} $$ Hence, from the second condition we infer $I\succeq A^*A$, which is another version of the desired property.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Nice demonstration. $\endgroup$ – user1551 Nov 30 '11 at 13:49

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.